OPINIONS OF THE MIDDLE EAST ON THE FORMATION OF PATRIOTIC FEELINGS IN YOUNG PEOPLE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The works and views of the thinkers of the Middle East have a significant value for the education of young people not only in their time, but also in modern society. Sense of patriotism, national and self-awareness play an important role in instilling in young people love for their homeland. This article analyzes the views of Middle Eastern thinkers on the formation of patriotic feelings.